A Multicenter, Open-Label, Randomized Phase II Controlled Study of rh-Endostatin (Endostar) in Combination with Chemotherapy in Previously Untreated Extensive-Stage Small-Cell Lung Cancer. Issue 1 (January 2015) - Lu, Shun; Li, Lu; Luo, Yi; Zhang, Li; Wu, Gang; Chen, Zhiwei; Huang, Cheng; Guo, Shuliang; Zhang, Yiping; Song, Xiangqun; Yu, Yongfeng; Zhou, Caicun; et al.
<x xml:space="preserve">Abstract</x> Background: Based on promising efficacy in a single-arm study, a randomized phase II trial was designed to compare the efficacy and safety of adding rh-endostatin (Endostar) to first-line standard etoposide and carboplatin (EC) chemotherapy for treatment of extensive-stage small-cell lung cancer. Methods: One hundred forty Chinese patients with pathologically confirmed, extensive-stage small-cell lung cancer were randomly assigned to EC alone or rh-endostatin + EC for 4–6 cycles, followed by single-agent rh-endostatin until progression or unacceptable toxicity. The primary endpoint was progression-free survival (PFS). The secondary endpoints included overall survival, Objective response rate (ORR), and quality of life. Results: Median PFS was 6.4 months with rh-endostatin + EC (n = 69) and 5.9 months with EC (n = 69) (hazard ratio 0.8 [95% confidence interval 0.6–1.1]). PFS was significantly higher with rh-endostatin + EC than with EC (hazard ratio 0.4 [0.2–0.9; p = 0.020]) in female. Median overall survival was similar in both groups (12.1 versus 12.4 months, respectively [p = 0.82]). ORR was higher in the rh-endostatin + EC group (75.4%) than in the EC group (66.7%) (p = 0.348). The efficacy of rh-endostatin + EC relative to that of EC was reflected by greater improvements in patient-assessed quality of life scores after 4 and 6 weeks of treatment. There was no difference between each regimen in the incidence of nonhematological or Grade III–IV hematological toxicities. Conclusions: Addition of rh-endostatin to EC for the treatment of extensive-stage small-cell lung cancer had an acceptable toxicity profile, but did not improve overall survival, PFS, and ORR.